2007
DOI: 10.2308/accr.2007.82.1.241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Auditors' Use of a Reciprocity-Based Strategy on Auditor-Client Negotiations

Abstract: Auditors face the challenging tasks of attesting that the financial statements are free from material misstatement while simultaneously fostering a functional working relationship with the client. As the financial statements may be considered, in part, a product of negotiations between the auditor and client management (Antle and Nalebuff 1991), the negotiation strategy employed by the auditor may be useful in effectively fulfilling both tasks. To investigate the effect of auditor strategy on the resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Ng and Tan (2003) focus on auditors and obtain the initial recommendations about potential accounting writedowns and the eventual outcomes of negotiations with clients. Sanchez et al (2007) investigate how auditor strategies during negotiations with the client affect the posting of significant audit adjustments, client satisfaction and client retention. Trotman et al (2005) compare the efficacy of three intervention methods that could be used by auditors to improve negotiation outcomes.…”
Section: S -Auditingmentioning
confidence: 99%
“…Ng and Tan (2003) focus on auditors and obtain the initial recommendations about potential accounting writedowns and the eventual outcomes of negotiations with clients. Sanchez et al (2007) investigate how auditor strategies during negotiations with the client affect the posting of significant audit adjustments, client satisfaction and client retention. Trotman et al (2005) compare the efficacy of three intervention methods that could be used by auditors to improve negotiation outcomes.…”
Section: S -Auditingmentioning
confidence: 99%
“…Our results cannot be fully explained by the extant negotiation-related theories in the accounting or general negotiation literature. For instance, the reciprocity mechanism has been found to be applicable to both auditors (Sanchez, Agoglia, and Hatfield 2007;Tan and Trotman 2010) and clients (Ng and Tan 2003;Hatfield, Houston, Stefaniak, and Usrey 2010). Our results showing that the use of the Gradual strategy leads to superior outcomes when used by either auditors or clients attest to the generalizability of the reciprocity mechanism across negotiation parties.…”
Section: Introductionmentioning
confidence: 56%
“…This early research on reciprocity as a way of inducing concessions from the opponent was later on picked up in the area of negotiations between auditors and clients, where e.g. Sanchez et al (2007) found that initial concessions by the auditor lead to reciprocal concessions by the client.…”
Section: Reciprocitymentioning
confidence: 98%